Regaining the dream how to renew the promise of homeownership for America's working families - Quercia, Roberto G. 1953-; Freeman, Allison; Ratcliffe, Janneke (Washington, D.C. Brookings Institution Press, 2011)
"Backed by extensive study of mortgage loans made to low-income Americans over a ten-year period, argues that in the wake of the financial crisis of 2008-09, lenders need not shy away from the low-income as risks but institute equitable and sustainable homeownership policies that include correctly structured loans"--Provided by publisher.
Foreclosing on the American dream -- Promoting sound, equitable homeownership -- Explaining the shadow mortgage system -- Lending for the long term -- Stress testing community reinvestment lending -- Ensuring sustainable homeownership -- Bringing community reinvestment lending to scale -- Regaining the dream.
Keywords: Housing -- United States -- Finance; Working class -- Housing -- United States; Mortgage loans -- United States; Homeownership -- United States